Multi-proxy approach involving ultrahigh resolution mass spectrometry and self-organising maps to investigate the origin and quality of sedimentary organic matter across a subtropical reservoir - Gontijo, Erik Sartori Jeunon [UNESP]; Herzsprung, Peter; Lechtenfeld, Oliver J.; de Castro Bueno, Carolina [UNESP]; A.C. Barth, Johannes; Rosa, André H. [UNESP]; Friese, Kurt (Elsevier, 2021)
Humic substances (HS) in sediments play an important role in carbon and nutrient biogeochemical cycles and fate of contaminants in the environment. However, information regarding HS quality and transformations that may affect their behaviour in reservoirs is still limited. The aim of this investigation was to track sources and changes in sedimentary HS across a subtropical reservoir, connecting them to in-lake processes and land-use influences. Surface sediments were collected at seven sampling sites in Itupararanga Reservoir (Brazil). Humic (HA) and fulvic (FA) acids (components of HS) were extracted from the sediment samples followed by in-depth characterisation via UV/VIS, fluorescence spectroscopy, elemental (C, N) and isotopic analysis (δ13C, δ15N), nuclear magnetic resonance (13C NMR) and Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). All data were analysed by self-organising maps. The results showed that samples from the upstream part of the reservoir were older and more decomposed. They likely originated from C3 land-plants (δ13C varied from −26.3‰ to −22.4‰), having more aromatic, oxygen-poor (O/C < 0.5) and unsaturated compounds (H/C < 1.1). In contrast, near-dam samples were younger and had larger contributions of autochthonous material. This was confirmed by oxygen-rich (O/C > 0.5) and partly more unsaturated compounds for FA as well as oxygen-poor and saturated compounds with H/C > 1.1 for HA. Self-organising maps pointed out these differences between upstream and dam areas and indicated that agriculture lands were related to microbially-derived HS. Changes in HS composition revealed that internal reservoir processes may have influenced HS quality across the reservoir.
Keywords: 13C NMR; FT-ICR-MS; Humic substances; Kohonen neural network; Source discrimination; Stable isotopes